Suggesting an Equation to Predict the Shear Strength of High and Low Strength Concrete Beams Without Stirrups Depending on Regression Analysis of Available Experimental Database - ALJUBAYLI, Nisrin (Latakia University Journal -Engineering Sciences Series, 2019)
Determining the shear strength of concrete is an important and complex problem in structural design, as the shear failure of concrete beams occurs suddenly, without warning. Most of countries have own Design codes, based on empirical equations to predict the shear strength of the concrete beam, as well as the equations suggested by many of researchers that aim to predict an accurate value of shear strength. This study presents an equation to predict the shear strength at failure of the high and low strength concrete beams, based on the regression analysis of experimental results of previous studies of 153 samples. In order to verify the validity of the proposed equation, a statistical study was conducted to compare the suggested equation with those in reference studies. The study showed that the proposed equation is conservative and gives more accurate values of the ultimate shear strength compared to others previous equations. يعتبر تحديد مقاومة البيتون على القص مسألة هامة ومعقدة في التصميم الإنشائي، باعتبار أن الانهيار على القص هو انهيار هش مفاجئ ويتأثر بالعديد من العوامل. لقد اعتمدت معظم البلدان في كوداتها التصميمية علاقات تجريبية لتوقع مقاومة الجوائز البيتونية على القص، كما يوجد العديد من العلاقات التي اقترحت من قبل بعض الباحثين بهدف الوصول لعلاقة تعطي قيمة دقيقة لمقاومة القص قريبة من القيم التجريبية. يقدم هذا البحث اقتراح علاقة لتوقع مقاومة القص الحدية لجوائز البيتون العادي والعالي المقاومة، وذلك بالاعتماد على تحليل الانحدار لنتائج تجريبية لأبحاث سابقة بلغ عددها 153 عينة جائزية. وللتحقق من صحة العلاقة المقترحة تم إجراء دراسة إحصائية للمقارنة بين هذه العلاقة والعلاقات الواردة في الدراسات المرجعية. بيّنت الدراسة أن العلاقة المقترحة هي علاقة محافظة وتعطي قيماً أكثر دقة لمقاومة القص الحدية مقارنة ببقية العلاقات الواردة في الدراسات المرجعية.